The Effectiveness of Cognitive-behavioral Therapy on Reducing the Depression as a Dysmenorrhea Symptom in Iranian Girls based on Randomized Control Trial (RCT) - Ghasemzadeh, Azizreza; Saadat, Maryam (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Depression is one of the most prevalent disorders among the girls with dysmenorrhea. The present research aimed to examine the effectiveness of cognitive-behavioral therapy on reducing the depression severity in primary dysmenorrhea among a selected group of Iranian girls in Tehran. Methods and Materials: The study was conducted in a Randomized controlled Trial (RCT)framework with pre- and posttest. The population included all 20 to 30 year old girls who were studying in Tehran University of Medical Sciences in 2015, among whom a total number of 73 applicants were conveniently selected. A primary interview through Beck Depression Inventory (BDI) was conducted to identify the Depression and dysmenorrhea in the sample. Finally, the sample decreased into 41 persons, among whom 34 applicants were randomly selected and divided into two groups of experimental and control, each of which with 17 people. The experimental group received the cognitive-behavioral therapy for nine sessions, each lasting for two hours while the control group received no treatment. The data were analyzed through inferential statistics such as Analysis of Covariance (ANCOVA) in SPSS, version 20. Findings: The mean scores for the experimental group dropped in posttest compared to the pretest while the mean score for the control group was not significant. Therefore, the cognitive-behavioral therapy could significantly differentiate between experimental and control groups (p<0.01). Conclusion: It can be concluded that cognitive-behavioral therapy could considerably impact on the reduction of depression severity in adolescent girls